BUSINESS TO BUSINESS (B2B) E-MARKETPLACE SEBAGAI MEDIA PROMOSI PRODUK USAHA KECIL DAN MENENGAH (UKM) - sur, Man (BBM (Buletin Bisnis & Manajemen), 2015)
AbstractB2B e-Marketplace is a media the promoted actor for Small and Medium Enterprises (SMEs) that has play role important to realize economic national structure in growing and developing SMEs ability to be strong and independent business, and can to increase build of region, employment generation, equity revenue and growing of ASEAN economic comminity. This research purposed to design website as media promoted product for SMEs and supplier at Bengkalis goverment used concept B2B e-Marketplace. Application B2B e-Marketplace stake the used developing approach such as system waterfall. The result of this research is design website e-Marketplace web-based integration, and can to give advantage for SMEs and supplier in to spread reach access promoted product with easy and cost relative cheap until it can increase competitiveness of businesses towards economic community of ASEAN.Â Keyword : B2B e-marketplace, product promotion, smes, supplier.